Endocannabinoids and the Processing of Value-Related Signals - Melis, Miriam; Muntoni, Anna Lisa; Pistis, Marco (Frontiers in Pharmacology, 2012)
Endocannabinoids serve as retrograde signaling molecules at many synapses within the CNS, particularly GABAergic and glutamatergic synapses. Synapses onto midbrain dopamine (DA) neurons in the ventral tegmental area (VTA) make no exception to this rule. In fact, the effects of cannabinoids on dopamine transmission as well as DA-related behaviors are generally exerted through the modulation of inhibitory and excitatory afferents impinging onto DA neurons. Endocannabinoids, by regulating different forms of synaptic plasticity in the VTA, provide a critical modulation of the DA neuron output and, ultimately, of the systems driving and regulating motivated behaviors. Because DA cells exhibit diverse states of activity, which crucially depend on their intrinsic properties and afferent drive, the understanding of the role played by endocannabinoids in synaptic modulations is critical for their overall functions. Particularly, endocannabinoids by selectively inhibiting afferent activity may alter the functional states of DA neurons and potentiate the responsiveness of the reward system to phasic DA.